A Cloud-Based Solution for Testing Applications' Compatibility and Portability on Fragmented Android Platform - Lanui, Ammar; Chiew, Thiam Kian (Proceedings / Asia Pacific Software Engineering Conference, 2019)
Testing is a vital activity in software development. The ISO/IEC has defined a standard for system and software quality models called ISO/IEC 25010:2011 to be a guideline and scope for testing any applications. Testing of mobile applications according to this standard, however, is more challenging than other types of software. The diversity of Android devices and various versions of Android operating system, for example, has created a large fragmentation of the Android platform. This fragmentation hinders testing of Android applications especially in relation to portability and compatibility. Existing solutions are either neglecting portability and compatibility issues or lack flexibility in fulfilling needs of the different organizations. We propose a cloud testing model to address the fragmentation of Android platform and provide automated application testing services on the actual devices. The model can be configured in the public, private or hybrid setups to suit individual organizations' needs and budget. A prototype was built based on the model. 10 Android testers used the prototype and the Android Emulator to perform mobile application testing. Results show that the model has the potential to manage the challenging portability and compatibility testing on the Android platform in a flexible and scalable manner.